2000
DOI: 10.1111/j.1365-2672.2000.tb05340.x
|View full text |Cite
|
Sign up to set email alerts
|

WaterborneEscherichia coliO157

Abstract: SUMMARY The waterborne route of Vero cytotoxin‐producing E. coli (VTEC) O157 infection was first suggested in two unconnected human cases in 1985. Since then, waterborne VTEC O157 has been identified in sporadic cases and in outbreaks of illness. Recreational waters, private and municipal supplies have been implicated from microbiological, environmental and epidemiological studies of cases. In addition, a research cohort study of farm workers identified exposure to private water supplies as a risk factor for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 29 publications
1
63
0
Order By: Relevance
“…A similar scenario is equally relevant for vermin, birds, and other wildlife likely to scavenge fields spread with wastes (1,11,23). Furthermore, leaving wastes on the surface increases the possibility that rainfall heavy enough to cause surface runoff could wash pathogens and manures directly into watercourses where they are likely to last longer than those in terrestrial environments (8,25,28,31,36).…”
Section: Vol 70 2004 Pathogen Decline In Livestock Wastes Spread Tomentioning
confidence: 99%
See 1 more Smart Citation
“…A similar scenario is equally relevant for vermin, birds, and other wildlife likely to scavenge fields spread with wastes (1,11,23). Furthermore, leaving wastes on the surface increases the possibility that rainfall heavy enough to cause surface runoff could wash pathogens and manures directly into watercourses where they are likely to last longer than those in terrestrial environments (8,25,28,31,36).…”
Section: Vol 70 2004 Pathogen Decline In Livestock Wastes Spread Tomentioning
confidence: 99%
“…Samples from each replicated field plot were collected over a 9-month period and analyzed independently. Samples of wastes that had been immediately incorporated were collected 0, 2,4,8,16,34,64,121, and 278 days after waste spreading. Wastes that had delayed incorporation or were not incorporated were sampled on days 0, 2, 8, 16, 64, and 121 days after waste spreading.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the confirmation of a presumptive causative agent involved in an outbreak is not always achieved (5). Moreover, the detection of non-O157 STEC strains is particularly difficult due to the lack of common phenotypic characteristics such as those presented by typical E. coli O157:H7 strains (delayed fermentation of sorbitol and the absence of ␤-glucuronidase activity).…”
mentioning
confidence: 99%
“…Studies have indicated that E. coli can survive for extended periods in manure and water (7,11). We have demonstrated that lettuce grown in soil containing contaminated manure or irrigated with contaminated water results in contamination of the edible portion of the lettuce plant.…”
mentioning
confidence: 99%